The Importance of a Physician’s Approach in Repetitive Physical Abuse of the Child and Sexual Abuse Occurring as a Result of Delayed Court Decision: A Case Report - Akbaba, Murat; Isır, Aysun Baransel; Şaştım, Mustafa Uğur; Tataroğlu, Zekeriya (The Bulletin of Legal Medicine, 2022)
Child abuse is an important problem seen all over the world. It is very important to identify the abused children in order to protect the health of the child and to get rid of repetitive abuse where the abuser is a member of the family. A girl was subjected to repetitive physical abuse was detected in the examinations. Although the necessary recommendations were made during the judicial reporting process, physical abuse continued due to the lack of action by the judicial authorities, and finally, sexual abuse was added. By sharing this case, it is aimed to emphasize the importance of the physician’s approach to the abuse cases and interdisciplinary cooperation between medicine branches, and also the importance of final court decisions and their effective role in the abuse. The importance and necessity of repetitive trainings and cooperation between medical-law-social institutionsin the management of child abuse has been put forward.